LOVE AND STRUGGLE OF THE MAIN CHARACTER AS REFLECTED IN CHARLES DICKEN’S GREAT EXPECTATIONS NOVEL: A PSYCHOLOGICAL STUDY - Fahrunnisa Fahrunnisa; Hikmah Pravitasari (English Didactic, 2021)
This paper discusses the novel "Great Expectations" by Charles Dickens which expresses the author's society "Victorian Age". It is clear that Dickens was much more successful than his predecessors in exposing the troubles of the society including class division and social struggle in the 19th century. The objective of this study is a psychological study of the main character “Pip” and the moral values from the story. The paper contains an introduction which expresses the role of literature in Victorian society. Moreover, it sheds light on Dickens and how he deals with the problems of Victorian society in Great Expectations. This paper entirely focuses on the struggle of the main character to find his dream as a gentleman and his love, the characterization of the main character, and moral values can be taken from the novel Great Expectations by Charles Dickens. It also consists of the conclusion sums up the findings of the paper.